Análisis morfológico y funcional de las puntas óseas “lengüetas de pájaro” de los contextos Goya-Malabrigo del Nordeste de Argentina - Loponte, Daniel Marcelo (2023)
Hollowed points locally known as “bird tongue” are bone artifacts recovered from Goya-Malabrigo assemblages of northeastern Argentina. For their manufacture, Myocastor coypus tibiae were used by hollowing out the proximal metaphysis to insert a shaft, and shaping by sawing/fracture and grinding the apical end. Their morphometric and microwear patterns suggest they were used as projectile points. Some of their characteristics, such as very sharp extended tip and weak hafting areas, propose they were subject to repeated rejuvenation processes with high discard rates. The rejuvenation process was focused on the tips, whose fracture produced smaller points with less sharp profiles that gradually decreased their effectiveness. These points appear to have been discarded when they were 4-5 cm in total length due to a decrease in efficiency. These tools could be underrepresented in archaeological assemblages due to analytical difficulty in identifying small fractured fragments and off-site replacement and discard.